Cellulases and hemicellulases from endophytic acremonium species and its application on sugarcane bagasse hydrolysis - Almeida, Maíra Nicolau de; Guimarães, Valéria Monteze; Bischoff, Kenneth M.; Falkoski, Daniel Luciano; Pereira, Olinto Liparini; Gonçalves, Dayelle S. P. O.; Rezende, Sebastião Tavares de (Appl Biochem Biotechnol, 2011)
The aim of this work was to have cellulase activity and hemicellulase activity screenings of endophyte Acremonium species (Acremonium zeae EA0802 and Acremonium sp. EA0810). Both fungi were cultivated in submerged culture (SC) containing L -arabinose, D -xylose, oat spelt xylan, sugarcane bagasse, or corn straw as carbon source. In solid-state fermentation, it was tested as carbon source sugarcane bagasse or corn straw. The highest FPase, endoglucanase, and xylanase activities were produced by Acremonium sp. EA0810 cultivated in SC containing sugarcane bagasse as a carbon source. The highest β-glucosidase activity was produced by Acremonium sp. EA0810 cultivated in SC using D -xylose as carbon source. A. zeae EA0802 has highest α-arabinofuranosidase and α-galactosidase activities in SC using xylan as a carbon source. FPase, endoglucanase, β-glucosidase, and xylanase from Acremonium sp. EA0810 has optimum pH and temperatures of 6.0, 55 °C; 5.0, 70 °C; 4.5, 60 °C; and 6.5, 50 °C, respectively. α-Arabinofuranosidase and α-galactosidase from A. zeae EA0802 has optimum pH and temperatures of 5.0, 60 °C and 4.5, 45 °C, respectively. It was analyzed the application of Acremonium sp. EA0810 to hydrolyze sugarcane bagasse, and it was achieved 63% of conversion into reducing sugar and 42% of conversion into glucose.
Keywords: Cellulase; Hemicellulase; Acremonium; Endophyte; Ethanol; Agroindustrial residue